Cold Process Dyeing by Soft Flow Method - Ashok Kumar, S.; Gowthaman, P.; Bharath, V.; Nikkhil, M. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The soft flow method of cold process dyeing is the subject of this research. Reactive dyes are a form of dye that is often used to colour cotton, viscose, and other cellulosic fibres. Reactive dyeing, on the other hand, necessitates a large amount of salt, water, and electricity. In addition, the procedure is slow, resulting in low fixation rates (approximately 75 percent). This necessitates several rinses to clear the unfixed ink, which consumes more water and energy (as rinse water is often heated). Reactive dyeing wastewater is difficult to process because it contains high amounts of salt and dye. Cold pad batch dyeing is a less resource- intensive alternative to reactive dyeing. Advantage of cold process method is reduced water consumption, energy consumption, high percentage of dye fixation, no salts were added, Better suited to stretch fabrics and knits because it is easier to manage tension control in a small machine and fabrics are stronger than bio polished equivalent. The disadvantage is that it takes a long time, and the procedure is only practical if high-quality equipment is used. It also necessitates an intermediate drying process after bleaching. We measured wash fastness, light fastness, and colour matching in this analysis and presented the findings.
Keywords: Reactive dyes; cold process dyeing; advantages; disadvantages; colour matching; wash fastness and light fastness